Endothelial injury and decline in lung function in persons living with HIV: a prospective Danish cohort study including 698 adults - Rønn, Christian; Knudsen, Andreas Dehlbæk; Arentoft, Nicoline Stender; Thudium, Rebekka Faber; Heidari, Safura-Luise; Sivapalan, Pradeesh; Ulrik, Charlotte S.; Benfield, Thomas; Ostrowski, Sisse Rye; Jensen, Jens Ulrik Stæhr; Nielsen, Susanne D. (Frontiers in Medicine, 2024)
ABSTRACT Objectives Endothelial injury may promote declining lung function. We aimed to investigate in well-treated persons living with HIV (PLWH) whether elevated levels of thrombomodulin (TM) and syndecan-1 (SDC1) are associated with excess lung function decline and worsening dyspnea. Methods A prospective cohort study comprising patients from the Copenhagen municipality. We included 698 PLWH with undetectable viral load. Biomarkers and demographics were measured at baseline, spirometry (forced expiratory volume in one second (FEV1) and forced vital capacity (FVC)) and dyspnea score both at baseline and 2-year follow-up. Both biomarkers were dichotomized at the 3rd quartile. Decline in lung function was estimated using a linear mixed model with patient-specific random effect. Increase in dyspnea score was estimated using a general mixed logistic regression model. Results We did not find an association between elevated SDC1 or TM and an excess decline in neither FEV1: SDC1: 4.5 mL/year (95% CI: -3.9 - 12.9, p=0.30), TM: 2.2 mL/year (95% CI: -6.0 - 10.4, p=0.60) nor FVC: SDC1: 4.1 mL/year (95% CI: -6.0 – 14.2 p=0.42), TM: 1.4 mL/year (95% CI: -8.3 – 11.1, p=0.78). A subgroup analysis of never-smokers was consistent with the main analysis. Likewise, we did not find any association between elevated SDC1 and TM and increase in dyspnea score: SDC1: OR 1.43 (95%CI: 0.89 – 2.30, p=0.14), TM: OR 1.05 (95%CI: 0.65 – 1.71, p=0.26). Conclusion We did not find a significant association between elevated biomarkers of endothelial injury and decline in lung function nor dyspnea.